660 Assessing the Benefits of Lifestyle Influences on Cardiovascular Health After Acute Coronary Syndrome (Balneo and PRM Research Journal, 2024)
The objective of our study was to explore the potential benefits of combining moderate alcohol consumption with regular vigorous physical activity on HDL-cholesterol levels and its potential positive impact on cardiovascular health. Materials and methods: The study comprised two groups: group A (102 patients) that consumed 10 grams of alcohol per day, specifically red wine, and increased their exercise levels in addition to their standard medical treatment, and group B (108 patients) which adhered only to their standard medical treatment. The patients were monitored for a year, during which various clinical parameters were observed. Results: Our study showed that moderate alcohol consumption, particularly red wine, along with increased physical activity levels, were associated with enhancements in exercise tolerance and elevated levels of HDL-cholesterol. Our findings suggest the efficacy of the intervention in improving lipid profiles, with the group that consumed alcohol as part of their treatment scheme, generally experiencing more pronounced positive effects. Statistically significant differences between groups in terms of angina evolution, acute myocardial infarction (AMI) recurrence, or arrhythmias evolution were not found. However, there were important differences in terms of ejection fraction (EF) improvement and quality of life, with the alcohol consuming group displaying greater improvements in both aspects. Conclusions: In conclusion, our study emphasizes the potential benefits of combining moderate alcohol consumption, specifically red wine, with increased physical activity levels for improving exercise tolerance and enhancing HDL-cholesterol levels. However, further research and clinical trials are essential to fully understand the mechanisms and optimize the integration of these lifestyle elements for improved cardiovascular health outcomes.